An Online System’s Effect on Iranians’ EFL Academic Writing Performance across Different Proficiency Levels - Ali Jahangard (Journal of English Language Teaching and Learning, 2020)
This study aimed to discover whether an online writing system has any effect on Iranians’ EFL academic writing performance. The study also sought to find out whether the proficiency level of learners influenced the effect of the system on academic writing. To meet this end, an online writing system was developed and 68 undergraduate students of the General English language course studying at Sharif University of Technology were requested to participate in this study. First, their English language proficiency was measured by a language proficiency test that included 80 questions of one of the latest versions of the official TOEFL iBT test, which was provided by the Educational Testing Service (ETS). Then, over an eight-week period, the participants were assigned to write eight versions of academic writing that followed a genre-based teaching approach through computer-based instructions. The writing scores were statistically analyzed and the results revealed that providing students with computer-assisted instruction (CAI) led to significant improvements in their academic writing performance. Moreover, according to the findings of this study, the learners’ level of proficiency did influence the effect of the system.